A Framework for Data Integrity Through Lineage Tracking in Cloud - Vadlamudi, Divya; K. Thirupathi Rao, Dr; Bodempudi, Sravani; Kadulla, Lavanya (International Journal of Engineering and Technology, 2018)
Cloud Computing [1] is a service oriented paradigm that pursuits at sharing resources to a large number of tenants. It's far approximately using internet to save, control and process facts in preference using personalized computer. Even though Cloud computing has the prerequisite to store the data; some users find some issues regarding safe data Storage in cloud. In that case metadata is the data that helps to determine the history of the particular data object we opted starting from its original resources. Here not only integrity of the data is proved but the specific lineage of data is also proved. Lineage is useful to know the origin of the data and its transformations in the cloud. In this paper we develop a framework to ensure Access control and data integrity using lineage of data stored in the cloud[2], and some general semantic definitions for integrity properties of lineage tracking. The main contribution of this paper is to explore framework through metadata for integrity and access control.Â Â